Reavaliação da via aérea do paciente obeso submetido à cirurgia bariátrica após a redução do índice de massa corpórea - Lima Filho, José Admirço; Ganem, Eliana Marisa [UNESP]; De Cerqueira, Bruno Gardélio Pedreira [UNESP] (Elsevier, 2011)
Reevaluation of the Airways of Obese Patients Undergone Bariatric Surgery after Reduction in Body Mass Index. Background and objectives: Difficulty intubating is a cause of mortality in anesthesiology and it can be related to obesity. The diagnosis of difficult intubation contributes for successful airways management. However, parameters that predict difficult airways are not well established. Mallampati classification, the interincisor gap, neck circumference, thyromental distance, and the presence of obstructive sleep apnea, are parameters that can indicate difficult intubation. Surgical treatment of obesity provides reduction in body mass index (BMI) with stabilization after about 2 years. The objective of the present study was to reevaluate the parameters described above and compare them with pre-surgical values. Methods: The BMI, Mallampati classification, neck circumference, interincisor gap, thyromental distance, and the degree of obstructive sleep apnea in polysomnography were evaluated in 51 patients of both genders in the preoperative period. Two years after the surgery and reduction of the BMI to < 35 kg.m-2, predictor factors of difficult airways were reevaluated by another anesthesiologist who knew the patients' BMI before surgery. Nine patients were excluded. The new reevaluation was performed, and for those who did not have another polysomnography the somnolence scale of Epiworth was applied. Results: Forty-two patients were reevaluated. They showed a reduction in BMI and neck circumference, and an increase in both interincisor gap and thyromental distance. Only one patient showed a reduction in Mallampati scale, and only 4 patients performed polysomnography. Conclusions: Reduction of the BMI allows for an increased interincisor gap, thyromental distance, and reduction in neck circumference. Mallampati classification remains the same. ©Elsevier Editora Ltda.
Reevaluation of the airways of obese patients undergone bariatric surgery after reduction in body mass index
Keywords: Airway management; Body mass index; Intubation; Obesity